Hakekat Pendidikan Pondok Pesantren: Studi atas Falsafah, Idealisme dan Manajemen Pendidikan Pondok Pesantren Al-Islam Kemuja Mendobarat Bangka - Sulaiman, Rusydi (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Pondok Pesantren has a spesific tradition that is far different with other institutions. It has sub-culture relating with way of life, system of values, system of power and authority in its administration. As the oldest education (indegenous) in Indonesia, ofcourse it had given high cultural and scientific contribution for community. Then the modernization changed the sub-culture and pillars of pesantren. In fact, many changed and a few of this institution withstood and reserved. This article analyzes Pondok Pesantren Al-Islam Kemuja as an educational institution in Bangka Belitung related to its basic aspects called “Philosophy and Idealism”, consist of basic values, pesantren’s traditional and its spirit (ruh al-Ma’had), also its institutional management. There are some aspects should be strenghened in pesantren: academic, administrative, net-working and so on Al-Islam has a special colour. Beside conserving its traditional values, this pesantren should be accomodative toward next valuable thing (al-Muhaafazah ‘alaa al-Qadiim al-Shaalih wa al-Akhdzu bi al-Jadiidi al-Ashlah). It is regarding that pesantren as fortresses for the defence of Islamic community and center for dissemination of Islam including Pondok Pesantren Al-Islam Kemuja which situated at small village, Kemuja Mendobarat Bangka Kepulauan Bangka Belitung.